(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Surgical site infections (SSIs) are the second most common nosocomial (hospital-acquired) infections after urinary tract infections. Despite recent advances in aseptic techniques, till now SSI has been considered as a major source of morbidity and mortality in developing countries and continued to represent about one fifth of all healthcare-associated infections. This cross-sectional study was conducted to analyze the pattern & aetiological factors of SSI among patients undergoing surgery at Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh involving 160 admitted patients during the study period. Of all SSIs, 73.0% were superficial and 27.0% were deep infections. Among the risk factors, Hypertension (29.4%), Diabetes Mellitus (24.4%), old age (>60 yr) [19.4%], anaemia (28.7%), and below average nutrition (13.8%) were the most common and had statistically significant relation with SSIs (p<.05). Moreover, incidence of SSIs was significantly higher in patients who required more duration of operation. The most common organism involved in SSI was S. aureas (42.4%), followed by E. coli (27.3%), P. aeruginosa (12.1%), bacteroids (12.1%) and Klebsiella spp. (6.1%). However, Meropenem was the most sensitive drug followed by Ceftriaxone according to culture and sensitivity screening. Gentamycin was 100% sensitive for gram-negative organism only. The incidence of SSIs are about one fifth of the post-surgical cases, where Staphylococcus aureus was the most prevalent organism. Meropenem and Gentamicin were the two most sensitive drugs against infections. BSMMU J 2021; 14(3): 50-56